Geographical analysis of health service centers in the municipality of Misrata using spatial analysis tools (Journal of Libya for geographical studies, 2024)
The study aims to conduct a geographical analysis of health service centers in the municipality of Misrata, to identify the pattern of their geographical distribution, the extent of their homogeneity with the distribution of the population, and the extent of the availability of this service in the municipal branches. The study used the descriptive analytical approach to suit the nature of the study and its objectives, which depends on collecting facts. Analyzing and interpreting it, and listing the factors affecting it, to give a clear picture of all aspects of the study and describe the reality of the phenomenon as it is, in addition to analyzing the data in an objective scientific analysis based on the spatial analysis tools available in the geographic information systems environment. The study found that the number of health centers in the municipality of Misrata reached (27) centers, distributed over an area of (18,765 square meters) within twelve municipal branches. The municipal branch, Shuhada Al-Rumaila, ranked first with (4) health centers, with an area of about (8,310 square meters). (44.28%) of the total area of health centers in the municipality. The study used spatial analysis tools available within the geographic information systems environment, through which it was concluded that the average and actual geographical center are located in the Tamina municipal branch, and that the two centers converge with a slight deviation of the actual spatial center towards the northwest of the virtual spatial center. The value of the standard score for health centers was (8482.9) at a confidence level of (0.05), while the nearest neighbor comparison was (854.3), which indicates a regularly spaced distribution pattern for health centers. The value of the distribution direction was (163.7) degrees from the north direction. With regard to the scope of the service’s influence, it was found that the areas of influence reached by the service amounted to (92.3 km2) of the area of the study area, which indicates the presence of (5,354.7 km2) of unserved area .
Keywords: health centers; geographical distribution; spatial analysis; nearest neighbor comparison; standard distans